Sumber Tenaga, Komunikasi, Usia, Lama Kerja Dan Pelatihan Perawat Dapat Meningkatkan Pelaksanaan Perawatan Bayi Prematur Di Ruang Perinatologi - Erna Julianti; Fajar Tri Waluyanti; Alleni dekania (STIKES Citra Delima Bangka Belitung, 2020)
Complexity of intensive care of premature babies causes some routine nursing cares are overlooked which may lead to extension of length of stay, risk of rehospitalization, additional disease’ complications, and decrease of parents’ satisfaction. This cross-sectional study aimed to identify factors related to the implementation of preterm infant care. the consecutive sampling technique was used to select 59 nurses caring for premature babies in the Perinatology Room at the Jakarta Hospital. The analysis was carried out univariately, and bivariately. The statistical test used is the Pearson test and linear regression. The results of the analysis found that there is a significant relationship between the source of nurses, communication, age, length of service of nurses, and training with the implementation of preterm baby care with p Value 0.014, 0.004, <0.001, <0.001, <0.001. Nursing care should be evaluated to improve the performance of nurses and the quality of care of premature babies